+++ title = "The Cyber Grabs CTF: Unbr34k4bl3 (942)" draft = true date = 2022-02-02 tags = ["ctf", "crypto"] languages = ["python"] layout = "single" math = true +++ Crypto challenge Unbr34k4bl3 from the Cyber Grabs CTF. > No one can break my rsa encryption, prove me wrong !! > > Flag Format: cybergrabs{} > > Author: Mritunjya > > [output.txt] [source.py] [output.txt]: ./output.txt [source.py]: ./source.py Looking at the source code, this challenge looks like a typical RSA challenge at first, but there are some important differences to note: - $N = pqr$ (line 34). This is a twist but RSA strategies can easily be extended to 3 prime components. - $p, q \equiv 3 \mod 4$ (line 19). This suggests that the cryptosystem is actually a [Rabin cryptosystem][Rabin]. - We're not given the public keys $e_1$ and $e_2$, but they are related through $x$. ## Finding $e_1$ and $e_2$ We know that $e_1$ and $e_2$ are related through $x$, which is some even number greater than 2, but we're not given any of their real values. We're also given through an oddly-named `functor` function that: $$ 1 + e_1 + e_1^2 + \cdots + e_1^x = 1 + e_2 + e_2^2 $$ Taking the entire equation $\mod e_1$ gives us: $$\begin{aligned} 1 &\equiv 1 + e_2 + e_2^2 \mod e_1 \\\ 0 &\equiv e_2 + e_2^2 \\\ 0 &\equiv e_2(1 + e_2) \end{aligned}$$ This means there are two possibilities: either $e_1 = e_2$ or $e_1$ is even (since we know $e_2$ is a prime). The first case isn't possible, because with $x \> 2$, the geometric series equation would not be satisfied. So it must be true that $\boxed{e_1 = 2}$, the only even prime. Applying geometric series expansion, $1 + e_2 + e_2^2 = 2^{x + 1} - 1$. We can rearrange this via the quadratic equation to $e_2 = \frac{-1 \pm \sqrt{1 - 4 (2 - 2^{x + 1})}}{2}$. Trying out a few values we see that only $\boxed{x = 4}$ and $\boxed{e_2 = 5}$ gives us a value that make $e_2$ prime. ## Finding $p$ and $q$ We're not actually given $p$ or $q$, but we are given $ip = p^{-1} \mod q$ and $iq = q^{-1} \mod p$. In order words: $$\begin{aligned} p \times ip &\equiv 1 \mod q \\\ q \times iq &\equiv 1 \mod p \end{aligned}$$ We can rewrite these equations without the mod by introducing variables $k_1$ and $k_2$ to be arbitrary constants that we solve for later: $$\begin{aligned} p \times ip &= 1 + k_1q \\\ q \times iq &= 1 + k_2p \end{aligned}$$ We'll be trying to use these formulas to create a quadratic that we can use to eliminate $k_1$ and $k_2$. Multiplying these together gives: $$\begin{aligned} (p \times ip)(q \times iq) &= (1 + k_1q)(1 + k_2p) \\\ pq \times ip \times iq &= 1 + k_1q + k_2p + k_1k_2pq \end{aligned}$$ I grouped $p$ and $q$ together here because it's important to note that since we have $x$, we know $r$ and thus $pq = \frac{N}{r}$. This means that for purposes of solving the equation, $pq$ is a constant to us. This actually introduces an interesting structure on the right hand side, we can create 2 new variables: $$\begin{aligned} \alpha &= k_1q \\\ \beta &= k_2p \end{aligned}$$ Substituting this into our equation above we get: $$\begin{aligned} pq \times ip \times iq &= 1 + \alpha + \beta + \alpha\beta \end{aligned}$$ Recall from whatever algebra class you last took that $(x - x_0)(x - x_1) = x^2 \- (x_0 + x_1)x + x_0x_1$. Since we have both $\alpha\beta$ and $(\alpha + \beta)$ in our equation, we can try to look for a way to isolate them in order to create our goal. $$\begin{aligned} pq \times ip \times iq &= 1 + k_1q + k_2p + k_1k_2pq \\\ k_1k_2pq &= pq \times ip \times iq - 1 - k_1q - k_2p \\\ k_1k_2 &= ip \times iq - \frac{1}{pq} - \frac{k_1}{p} - \frac{k_2}{q} \end{aligned}$$ $\frac{1}{pq}$ is basically $0$, and since $k_1$ and $k_2$ are both smaller than $p$ or $q$, then we'll approximate this using $k_1k_2 = ip \times iq - 1$. Now that $k_1k_2$ has become a constant, we can create the coefficients we need: $$\begin{aligned} \alpha + \beta &= pq \times ip \times iq - 1 - k_1k_2pq \\\ \alpha\beta &= k_1k_2pq \end{aligned}$$ $$\begin{aligned} (x - \alpha)(x - \beta) &= 0 \\\ x^2 - (\alpha + \beta)x + \alpha\beta &= 0 \\\ x &= \frac{(\alpha+\beta) \pm \sqrt{(\alpha+\beta)^2 - 4\alpha\beta}}{2} \end{aligned}$$ Putting this into Python, looks like: ```py >>> k1k2 = ip * iq - 1 >>> alpha_times_beta = k1k2 * pq >>> alpha_plus_beta = pq * ip * iq - 1 - k1k2 * pq >>> def quadratic(b, c): >>> disc = b ** 2 - 4 * c >>> return (-b + sqrt(disc)) / 2, (-b - sqrt(disc)) / 2 ``` I'd like to thank @10, @sahuang, and @thebishop in the Project Sekai discord for doing a lot of the heavy-lifting to solve this challenge. [Rabin]: https://en.wikipedia.org/wiki/Rabin_cryptosystem